YouTube audience sentiment and discourse on the Watchdoc documentary “Tak Ada Makan Siang Gratis” (No Free Lunch) - Dimas Septo Nugroho (C-DISC, 2026)
This study examines audience sentiment and discursive responses to the framing of Indonesia’s Free Nutritious Meal (MBG) program in the Watchdoc documentary Tak Ada Makan Siang Gratis (No Free Lunch) on YouTube. Using an explanatory sequential mixed-methods design, it analyzed a corpus of 1,551 comments and replies through the IndoBERT language model, complemented by systematic manual validation and Critical Discourse Analysis (CDA) to identify audience narrative positions. The findings reveal a strong predominance of negative sentiment (83.24%), with the government emerging as the primary discursive target (67.70%). Furthermore, 89.23% of participants supported the documentary’s critical framing, while legitimation (44.87%) was the dominant communicative function, reflecting users’ efforts to reinforce the documentary’s evidentiary and argumentative claims. The study concludes that the documentary effectively performed an agenda-setting function by transforming the state’s benevolent welfare narrative into a site of material grievance and institutional distrust. This research contributes to the literature by integrating IndoBERT with culturally sensitive manual validation to address sarcasm and code-switching in Indonesian digital discourse and by introducing the concept of the negotiated legitimation zone to explain the political ambivalence of audiences in emerging democracies.